Study of hybrid thermal system with photovoltaic panels using virtual instruments. (July 2020) - Popov, Rumen; Paunkov, Nikolay; Rangelova, Vania; Georgiev, Aleksandar
Abstract: In this paper, а novel set of virtual instruments has been developed and approved. It allows for providing on-line or off-line uncertainty calculations and statistical hypothesis testing. A novel instrument "Expansion card" has been developed in our laboratory. Several tests were performed to check the performance of some hybrid heating installation components. For this purpose, a hybrid solar thermal system, combined with photovoltaic panels has been designed and constructed by the authors. The system consists of two basic subsystems: thermal part and electrical part. Both are equipped with measuring devices to form a complex virtual test instrument. The aim of the tests was to characterize the energy efficiency of a low-cost PV/T panel construction and to check the proper operation of the developed virtual instrument tools. The tests showed that there was poor thermal contact between the pipe and the backside of the cell's plate. That lead to the modification of the PV/T panel's construction. It was also found that at higher temperatures, the heat exchange in the PV/T panel deteriorates and its energy output is better. So the parallel connection should be preferable for PV/T panel heat exchangers. Highlights: A hybrid system with combined PV/T panels was designed and experimentally tested. Sophisticated methods for data set analyses using SCADA system were approved. A set of virtual instrument tools has been developed and field tested. The set allows uncertainty calculation and statistical hypothesis testing.